1985
DOI: 10.1007/bf01739671
|View full text |Cite
|
Sign up to set email alerts
|

Mild proteinuria in patients with unilateral kidney

Abstract: Arterial blood pressure, 24 h urinary excretion, and glomerular filtration rate (GFR) in 24 patients with unilateral kidney were compared with an age and sex matched control group of healthy persons. Of the patients with unilateral kidney, 13 were uninephrectomized and 11 patients had a congenital unilateral kidney. The 24 h urinary protein excretion in patients with one kidney was significantly higher (630 +/- 51 mg/24 h) compared to the control group (206 +/- 36 mg/24 h). The arterial systolic and diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Brenner and Mackenzie [5] stated that individuals with URA, who have hyperfiltration from birth, tend to develop proteinuria or systemic hypertension only after their 3rd decade. This theory is supported by reports showing that in adult patients with URA, there is a higher prevalence of albuminuria, proteinuria, hypertension, and renal insufficiency than in the normal population and that these abnormalities are more frequent after a longer follow-up period [24][25][26][27][28] . However, it has to be mentioned that other studies could demonstrate that adults with a solitary kidney since childhood had no adverse effects of longstanding hyperfiltration [29,30] .…”
Section: Discussionsupporting
confidence: 66%
“…Brenner and Mackenzie [5] stated that individuals with URA, who have hyperfiltration from birth, tend to develop proteinuria or systemic hypertension only after their 3rd decade. This theory is supported by reports showing that in adult patients with URA, there is a higher prevalence of albuminuria, proteinuria, hypertension, and renal insufficiency than in the normal population and that these abnormalities are more frequent after a longer follow-up period [24][25][26][27][28] . However, it has to be mentioned that other studies could demonstrate that adults with a solitary kidney since childhood had no adverse effects of longstanding hyperfiltration [29,30] .…”
Section: Discussionsupporting
confidence: 66%
“…In the 1980s, papers by Hostetter et al (35) and others (9) on the consequences of surgical ablation of renal mass sparked new interest in the fate of the living kidney donor. Indeed a number of reports appeared that showed the development of proteinuria in persons with a single kidney (16,20,36) and former kidney donors (10,14). Some authors also found a significant increase in blood pressure after renal donation (9,15,37).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the amount of protein excreted by the remaining kidney, especially in male donors (14–16), has been found repeatedly (17–21). But in the absence of a correlation between protein excretion and blood pressure or renal function, the clinical significance of this finding remains unclear (12,14,22,23).…”
Section: Introductionmentioning
confidence: 90%
“…However, after approximately 20 years no kidney dysfunction was found in these patients. Oberle et al [39] observed over three-times increased proteinuria in patients after nephrectomy. None of our children developed pathological proteinuria.…”
Section: Discussionmentioning
confidence: 98%